The Influence Of Capital Structure And Financial Performance On Company Value In Registered Banking Companies On The Indonesian Stock Exchange - Novitaria Sipayung; Shabrina Tri Asti Nasution; Sari Bulan Tambunan (Jurnal Scientia, 2024)
The aim of this research is to determine the influence of capital structure and financial performance on banking companies listed on the Indonesia Stock Exchange in 2020-2022. The design of this research is an associative approach. The population in this study was 46 banking companies listed on the Indonesia Stock Exchange in 2020-2022 with a sampling technique using the proportional sampling method, so that the sample obtained was 31 companies with a research period of 3 years so that the total observation data amounted to 93 company financial report data. banks listed on the Indonesian Stock Exchange in 2020-2022. The data analysis method uses multiple linear regression analysis. The research results show that partially capital structure has a negative and significant effect on company value, financial performance has a positive and significant effect on company value, and simultaneously capital structure and financial performance have a positive and significant effect on company value.